Dynamic shift of malaria cases in northwest Ethiopia: a 10-year retrospective cohort data analysis from 2012 to 2021 - Abere, Aberham; Ayalew, Solomon; Wondale, Bealemlay; Tigabu, Fentahun; Gizachew, Nigus; Tesfaye, Takele; Ayalew, Getnet; Tegegne, Banchamlak; Melaku, Mulat Yimer; Aschale, Yibeltal; Tilahun, Adane; Tamir, Mebratu; et al. (Frontiers in Malaria, 2025)
BackgroundDespite the WHO’s extensive efforts to eliminate malaria from sub-Saharan Africa, including Ethiopia, it remains the most serious public health issue, with seasonal variations and high mortality. This study aimed to assess the 10-year trend in the prevalence of malaria in northwest Ethiopia.MethodsA retrospective study was carried out at the Maraki Health Center, northwest Ethiopia. Blood film results from a 10-year period (from January 2012 to December 2021) were recorded using a data extraction sheet, with data sourced from a laboratory logbook. The 10-year trend of malaria incidence was observed by year, month, and season, with respect to age and gender. The species distribution of the causative agents was determined in the study area.ResultsOver 10 years, 15,978 blood films were requested for malaria diagnosis, and 57.5% were from male respondents. Approximately 68.0% of the respondents were under the age group of 15 years old. The mean prevalence rate of malaria was 25.2% (n = 4,019) (95% CI: 23.83–26.59). The highest peaks of total malaria cases were observed in 2012 and October, whereas the lowest peaks were observed in 2016 and April (mean annual case = 401.9). Plasmodium falciparum was the dominant malaria species throughout the 10-year study period. The highest and lowest Plasmodium vivax counts were observed in 2012 and 2018, respectively.ConclusionThe study revealed a drop in annual transmission rates in 2016–2017; however, to date, there has been a gradual rise. Moreover, shifts in the predominant malaria species were observed in 2012, 2014, and 2015, with P. falciparum as the dominant species. Sustained efforts are still essential to decrease the transmission of malaria to a level where it no longer threatens public health.